The Paul Storer Memorial Lecture - Cross-Border Trade Integration and Monetary Policy - Stephen S. Poloz; Paul A. Storer (Bank of Canada, 2016)
In this paper we explore the nexus between cross-border trade integration and monetary policy. We first review the evidence that trade liberalization has increased the degree of integration in North America and conclude that, while robust structural inferences remain elusive, there is sufficient supporting evidence for central banks to treat the issue seriously. The paper then discusses several channels by which increased integration might affect macroeconomic models. We introduce modifications to the Bank of Canada's main policy model, ToTEM, to capture some of the impacts of integration suggested in the literature and generate stochastic simulations to compare versions of the model with low and high integration. The main conclusion is that increased integration may make it more challenging for central banks to control inflation, in the sense that doing so will require more variability in interest rates, exchange rates and the output gap.
Keywords: E37; E5; F1; F41; F6; 330; Economic Models; Monetary Policy; Trade Integration